2001
DOI: 10.2114/jpa.20.293
|View full text |Cite
|
Sign up to set email alerts
|

Human gastrocnemius medialis Pennation Angle as a Function of Age: From Newborn to the Elderly.

Abstract: The aim of the present study was to quantify changes in human skeletal muscle pennation angle (F θ ) values during growth and adult life. The human gastrocnemius medialis muscle of 162 subjects (96 males and 66 females) in the age range 0-70 years was scanned with ultrasonography. The subjects were laying prone, at rest, with the ankle maintained at 90° with all muscles relaxed. F θ increased monotonically starting from birth (0 years) and reached a stable value after the adolescent growth spurt. There was a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 23 publications
4
62
0
3
Order By: Relevance
“…Possible candidates in healthy children include changes in innervation, muscle architecture and muscle contractile properties with growth (6;12;15;21). Upper extremities nerve conduction velocity increases with age in children and may be related to thinning of the distal compared to proximal portions of the axons as limbs grow in length (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible candidates in healthy children include changes in innervation, muscle architecture and muscle contractile properties with growth (6;12;15;21). Upper extremities nerve conduction velocity increases with age in children and may be related to thinning of the distal compared to proximal portions of the axons as limbs grow in length (15).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing force-versus-time relationships during single muscle contraction in children and adults, Going et al (12) showed maximal rate of force production and time to reach maximal force were lower in children indicating changes in muscle contractile properties occur with normal growth. Lastly, muscle angle of pennation changes as a child grows (6) possibly affect strength development. Either alone or in concert, any of these variables could affect changing patterns of muscular force production during growth in children.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Larger pennation angles accommodate a larger number of shorter muscle fibres than smaller pennation angles. [45][46][47] The pennation angle is not fixed but increases when the muscle fibres shorten, either from a reduction in joint angle or during isometric contractions. Thus pennation angle influences effective CSA, and, where possible, a measurement of pennation angle should be included to correct anatomic CSA, providing a measure of physiologic cross-sectional area (PCSA).…”
Section: Muscle Fibre Lengthmentioning
confidence: 99%
“…The mechanisms underpinning the development of age-related gains in muscular strength include neuro-maturation (Savelsbergh, 2003), increases in muscle size (Kanehisa et al, 1995;Morse et al, 2008), changes in muscle architecture (Binzoni et al, 2001) and increases in moment arm length (Wood et al, 2006;Morse et al, 2008;O'Brien et al, 2009).…”
Section: Introductionmentioning
confidence: 99%